Lignite Basins in Poland after 1945 - Kaliński, Janusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
Lignite mining in Poland started after World War Two, as a result of the change ofwestern borders. Until the 1970 s, the Lower Silesian Turoszów Basin played the primary role, despite competition from the Konin Basin in Greater Poland. In 1978 both basins, together with several smaller mines, provided 41 m tonnes of lignite. Ten years later the number rosę to 73,5 m tonnes, mostly thanks to investments in the centrally located Bełchatów Basin, which has sińce dominated the sector. Overall production never recovered after 1989, with Poland falling from the 5th, to the 8th place among the largest lignite extractors between 1989 and the beginning of the 21st century. Recently about one third of the energy in Poland has been based on lignite, similarly to Bułgaria, Romania and Turkey (while in the Czech Republic, Serbia, and Montenegro it has amounted to 69%).